UNDERSTANDING CONSUMER PERCEPTION WITH RESPECT TO TEA BRAND USING PLS ALGORITHM - band, gayathri swapnil; Shah, Neeta Vijay (Journal of Contemporary Research in Management (JCRM), 2014)
The study regarding Consumer buying behavior is causal in nature and is aimed at evaluating the impact of marketing mix on minds of the consumer. General customer residing at Nagpur and Wardha constituted the population for the study. Simple Random sampling technique was used to identify responses for the study and a sample size of 396 respondents from Nagpur and 130 respondents from Wardha was taken to conduct the study. Self-designed questionnaire was used for evaluating Marketing mix for tea branding. The PLS algorithm estimates path models using latent variables. It examines the â€œstructureâ€ of interrelationships expressed in a series of equations, similar to a series of multiple regression equations. On conclusion the GoF index was 0.52079 meaning that the model had acceptable predictive relevance. We can find well researched relaunch of Sapat 2003 onwards as per the consumer perception for the success of the brand.